Long-term immunogenicity of the SA14-14-2 Japanese encephalitis (JE) vaccine (CD.JEVAX®) booster following chimeric JE (IMOJEV®) vaccine priming in Thai children - Tawee Chotpitayasunondh; Piyarat Suntarattiwong; Sutee Yoksan (Taylor & Francis Group, 2024)
Japanese encephalitis (JE) is a significant public health concern in Asia, particularly in children, where vaccination plays a crucial role in prevention. In this study, we investigated the immunogenicity and safety of two different live-attenuated JE vaccines used as primary and booster doses. Fifty healthy participants aged 1-3 years, who were primed with the chimeric JE vaccine IMOJEV® a year earlier, received a booster dose of the SA14-14-2 JE vaccine CD.JEVAX®. To evaluate the immune response, JE-neutralizing antibody titers were assessed on day 0 (pre-booster), day 30, and annually from 1 to 5 years post-booster using the 50% plaque reduction neutralization test (JEPRNT50). The assessment revealed strong immunogenicity 30 d post-booster, with a geometric mean titer of 2092.4 [95% confidence interval (CI): 1473.9-2970.5] and a seroprotection rate of 100%, which gradually decreased to 97.5% at 5 years post-booster. No severe adverse events were observed. The most common reaction within 7 d of vaccination was fever (20%; 95% CI: 10.7-32.3). These results indicate that a booster dose of CD.JEVAX® elicits a strong immune response in children previously vaccinated with IMOJEV® while maintaining a good safety profile, thus supporting the interchangeability of these two live-attenuated JE vaccines. Registered at www.thaiclinicaltrials.org (TCTR ID: TCTR20221102003), our study suggests that CD.JEVAX® can be a viable option for booster vaccination in JE prevention programs, potentially enhancing vaccine flexibility and accessibility.